2020
DOI: 10.1155/2020/4813140
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Noncoding RNAs in the Differentiation of Osteoclasts

Abstract: As the most important bone-resorbing cells, osteoclasts play fundamental roles in bone remodeling and skeletal health. Much effort has been focused on identifying the regulators of osteoclast metabolism. Noncoding RNAs (ncRNAs) reportedly regulate osteoclast formation, differentiation, survival, and bone-resorbing activity to participate in bone physiology and pathology. The present review intends to provide a general framework for how ncRNAs and their targets regulate osteoclast differentiation and the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 204 publications
0
4
0
Order By: Relevance
“…miRNAs were stated to have relevant effects in controlling osteoclast differentiation. Research reported that an increase of miR-125a-5p augmented osteoclast differentiation through blocking TNFRSF1B expression [ 74 ], while Zhou et al demonstrated that the increase of miR-100-5p avoided bone loss in ovariectomized animals through reducing the production of FGF-21 and osteoclast activeness [ 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs were stated to have relevant effects in controlling osteoclast differentiation. Research reported that an increase of miR-125a-5p augmented osteoclast differentiation through blocking TNFRSF1B expression [ 74 ], while Zhou et al demonstrated that the increase of miR-100-5p avoided bone loss in ovariectomized animals through reducing the production of FGF-21 and osteoclast activeness [ 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…Non-coding RNAs (ncRNAs) are a crucial type of RNA that are involved in various genetic and epigenetic processes such as transcriptional and post-transcriptional regulation ( Geng et al, 2018 ; Panni et al, 2020 ). Interestingly, despite the fact that only 10% of the genome codes for proteins, most of it is transcribed into functional non-coding RNAs ( Zhao et al, 2020 ). NcRNAs can be classified into basic structure and regulatory types, and they play a significant role in both physiological and pathological processes ( Li M. et al, 2018 ), including the regulation of neuropathic pain and activation of Wnt/β-catenin signaling in the spinal cord ( Sun et al, 2018 ; Cui et al, 2019 ; Zhang S. B. et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…By attaching to its receptor, RANK, RANKL plays a critical role in regulating mature osteoclast development, function, and survival. Moreover, osteoclastogenesis relies on the transcriptional activity of NFATc1, cathepsin K (CTSK), and c‐Fos, all of which are triggered by the nuclear factor‐κB (NF‐κB) signaling pathways, which are mobilized in part thanks to RANK recruitment (Yu et al, 2015 ; Zhao et al, 2020 ). Therefore, it is imperative to suppress RANKL‐induced downstream signaling pathways.…”
Section: Introductionmentioning
confidence: 99%